PUBLIC KNOWLEDGE ABOUT DIABETES MELLITUS IN THE WORKING AREA OF PUSKESMAS PUCANG SEWU SIRABAYA CITY - Alberta, Lembunai Tat; Endang Soelistyowati; Irine Christiany; Alifia Mei Sanida (Global Ten Public Health and Nursing Journal, 2024)
Abstract Diabetes Mellitus is a chronic metabolic disease characterized by increased levels of sugar in the blood. Knowledge about Diabetes Mellitus is fundamental in efforts to handle diabetes mellitus and can affect people's behavior in their lifestyle and activities. The purpose of this study is to determine public knowledge and factors related to public knowledge about Diabetes Mellitus in the working area of Pucang Sewu health center Surabaya. Method: Analytical descriptive research with a sample of 110 people. Data collection using interview method using questionnaire, descriptive and analytical data analysis using Q-Square test. Results: The results showed 39.1% had less knowledge, 16.4% had good knowledge, and 44.5% had enough knowledge. There was a significant relationship between the level of education and public knowledge about diabetes mellitus and there was no significant relationship between gender, age and occupation with public knowledge about diabetes mellitus. Conclusion: Almost half of the people in the working area of Pucang Sewu health center in Surabaya have less knowledge about Diabetes Mellitus, the level of education is related to public knowledge about diabetes mellitus, while the factors of gender, age and occupation are not related to public knowledge about diabetes mellitus. Recommendation: The need to involve various parties including the community in increasing knowledge about diabetes mellitus by using various methods and paying attention to the age, gender and work of the community.